A igualdade $$\sum_{k=0}^{n}(-1)^{k}\left(\begin{array}{l} n \\ k \end{array}\right) 7^{n}+\sum_{j=0}^{m}\left(\begin{array}{c} m \\ j \end{array}\right) 2^{m}=64$$ é válida para:


img
ITA IIIT 18/11/2021 17:52
Se você conhece a Fórmula do Binômio de Newton, a questão é bem direta:\begin{matrix} (a+b)^n = \sum_{k=0}^{n} {n \choose k} . a^{n-k}.b^k \end{matrix}Analisando por partes, primeiro: \begin{matrix} \sum {n \choose k} . 7^{n}.(-1)^k &\Rightarrow& \sum {n \choose k} . 7^{n-k}.7^k.(-1)^k &\Rightarrow& \sum {n \choose k} . 7^{n-k}.(-7)^k &\therefore& (0+0)^n = 0 \end{matrix}Segundo: \begin{matrix} \sum {m \choose j} . 2^{m} &\Rightarrow& \sum {m \choose j} . 2^{m-j}.2^j &\therefore& (2+2)^m = 2^{2m} \end{matrix} Então, \begin{matrix} 0 + 2^{2m} = 64 &\Rightarrow& 2^{2m} = 2^6 &\Rightarrow& 2m = 6 &\therefore &m = 3 \end{matrix} \begin{matrix} Letra \ (B) \end{matrix}
Modo de Edição
0 / 5000
ManualLaTeX